Contraception-still miles to go: a study among married women in a rural area of West Bengal - Pal, Jayita; Ahmad, Shamshad; Siva, Arohita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unregulated growth of population is the most important problem that is hindering the socio-economic growth of a developing country like India since its independence. Multiple socio-economic factors are responsible for non-acceptance of contraception. To meet the unmet need these factors are needed to be explored. The current study aimed to assess the rate of acceptance of different contraceptive methods, various socio-demographic factors affecting acceptance and to find out the reasons for non-acceptance among married women of reproductive age group in a rural area of West Bengal. Methods: An institution based cross sectional study was conducted among 224 married women of reproductive age group with the help of a predesigned, pretested schedule. Results: Almost entire study population (98.2%) had the knowledge of any modern accepted method of contraception; health personnel (91.1%) being the most common source of knowledge. In majority of cases (69.6%) the decision of contraceptive use was taken by the husband and wife jointly. The overall prevalence of current use of contraception was 33.9% of which most common method adopted was found to be tubectomy (42.1%). The total unmet need was 50%. Multivariate analyses revealed that women aged more than 27 years, belonging to Hindu religion, nuclear family of higher per capita income with education of self and husband being up to or above middle level, having at least two leaving issue and one male child had higher odds of ever use of contraception. Conclusions: To bridge the gap of knowledge and practice intense awareness generating programmes focusing on the local barriers of contractive practice were the need of the hour to address this alarming public health problem.